Treatment Modalities and Survival in Older Adults with Metastatic Colorectal Cancer in Real Life. Issue 5 (6th March 2019) - Gouverneur, Amandine; Bezin, Julien; Jové, Jérémy; Bosco‐Lévy, Pauline; Fourrier‐Réglat, Annie; Noize, Pernelle
Abstract : OBJECTIVES: Metastatic colorectal cancer (mCRC) is increasingly treated with targeted therapies, but little is known about real‐life mCRC treatment in older adults. The aims were to describe the real‐life first‐line treatment modalities in older adult mCRC patients, to identify factors associated with treatment modalities, and to evaluate survival with regard to treatment modalities. PATIENTS AND METHODS: A cohort of mCRC patients aged 65 years and older at diagnosis was identified between 2009 and 2013 using French national healthcare insurance system claims data. Treatment modalities were: treatment with one or more anticancer medication vs best supportive care and, among treated patients, treatment with targeted therapy vs conventional chemotherapy alone. Multivariate logistic regression was used to identify factors associated with treatment by anticancer medication and by targeted therapy. Cox proportional hazards models were used to assess the independent effect of treatment modalities on overall survival while adjusting for baseline covariates identified with logistic regression. RESULTS: A total of 503 patients were included with a median age of 78 years (54% were men). Of these, 299 (59%) were treated with anticancer medications. Among treated patients, 131 (44%) received targeted therapy. In multivariate analysis, age 75 years or older, renal failure, malnutrition, and five or more concomitant medications were associated with a lower likelihood of treatment with anticancer medications. Among treated patients, age 75 years or older, history of cancer, lymph node metastases, and a single metastatic site were associated with a lower likelihood of treatment with targeted therapy. Multivariate Cox proportional hazards models found that treatment with any anticancer medication tended to be associated with a lower risk of death; treatment with targeted therapy was not significantly associated. CONCLUSION: A more appropriate prescription of anticancer medications in the older adult will require the definition of more explicit criteria to avoid undertreatment. The real benefit of targeted therapies vs conventional chemotherapy alone needs to be confirmed in this population. J Am Geriatr Soc 67:913–919, 2019.